PENINGKATAN AKTIVITAS SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN DENGAN TYPE JIGSAW SDN 19 BENGKAYANG - Kristiawan, Jimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aimed to describe the improvement of students' learning activities through cooperative learning Type Jigsaw on subjects Civics class IV SDN 19 Melabo Bengkayang.The method used in this research is descriptive, form research is classroom action research, the nature of the research is a collaborative research subject is the teacher who taught in the fourth grade SDN 19 Melabo, Bengkayang, and students who totaled 15 people consisting of seven schoolgirls girls and 8 boys. Research procedure includes four stages: Planning, Implementing, Observations and Reflections.This study was conducted by two cycles. The results of the research are: 1) The ability of teachers plan learning in the first cycle by an average of 1.83 and the second cycle an average of 3.36 an increase of 1.53. 2) The ability of teachers to implement learning with an average of the first cycle of 1.63 and averaged 3.64 second cycle there is an average increase of 2.01. 3) Nilaiaktivitas students' average score on the first cycle of 51.44% and the average value of the second cycle of 76.77% No 25.33% increase.   Keywords: Type Jigsaw, Learning Activities, Civic Education.